Kajian Struktural Sastra Bandingan Cerita Jaka Tarub dan Cerita Watu Wari Labu dan Implikasinya Bagi Pendidikan Anak - Larasati, Maria Marietta Bali; Sareng, Anselmus Nong (Program Studi Pendidika Bahasa dan Sastra Indonesia, 2021)
Structural studies aim to dismantle and expose as carefully, in detail, and as deeply as possible the interrelationship and interrelationship of all elements and aspects of literary works that together produce overall meaning. Comparative literature is a study to compare literature with literature, or literature with other fields. This study aims to describe the similarities and differences between the folklore of Jaka Tarub from Central Java and the folklore of Watu Wari Labu from Bajawa. The study used in this study is a structural study of comparative literature. This study used descriptive-comparative meeodes. The theory used is comparative literary theory. The results and discussion of this study show that in terms of structure there are 1) similarities and differences between the folklore of Jaka Tarub from Central Java and the folklore of Watu Wari Labu from Bajawa, 2) the pattern of the story, and 3) the implications for children's education